Legal Policy on the Use of Heir Certificates (SKAW) for Registration of Land Rights Transfers in Indonesia - Silviana, Ana; Fuadi, Ariza (LAW REFORM, 2023)
One of the requirements for the process of changing names in the transfer of land rights due to inheritance is to be proven by a Certificate of Heirship (SKAW). As a result of the pluralism of the civil law system in Indonesia, land policy in processing land registration due to inheritance requires the SKAW to be made by three institutions; the SKAW made by the Village Head/ Lurah and Authentic Deed by Notary, and the SKAW from the Inheritance Property Center for each population group is different. The enactment of the Population Law has eliminated racial discrimination in population classifications, leaving only Indonesian citizens and foreigners. This article aims to understand land law policies related to the making of SKAW after the Population Law and its legal force. The approach used to analyze the problem was a doctrinal approach using secondary data through legal materials. The results of the analysis show that the Indonesia's land law policy in implementing land registration due to inheritance after the Population Law no longer requires the creation of the SKAW according to population classification. It has an impact on the legal force of each SKAW legal product made by three officials, which is a binding legal product as a condition for registering land rights due to inheritance and can be used as evidence in court trials.